YouTubers, Online Selves and the Performance Principle: Notes from a Post-Jungian Perspective - Singh, Greg (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
Of the many challenges facing the field of media studies today, the rapid acceleration of the media ecosystem through which people communicate, share and indulge, and seek escape from the tedium of everyday life, presents a set of specific problems. The contemporary media landscape is both an extension and a continuation of more traditional forms and objects for analysis, and also an arena that has, arguably, radically redefined the discipline in terms of the innovations and stark changes to technology, institutions and financial arrangements that have shaped the world of media and communications as we know it. A key area in which post-Jungian approaches are well-placed to accommodate is in the fast-changing field of online media celebrity. The meteoric rise in popularity of YouTube vloggers has given new impetus to the fields of celebrity studies and persona studies –redefining the popular understanding of how celebrity status is sought, conferred, and consumed; and ultimately, transforming how celebrity is defined as a notion. Using critical inquiry as a method, this article discusses mediatised notions of self, persona, and self-commodification from post-Jungian and relational perspectives. The discussion from these theoretical perspectives will open vistas into the critical study of digital, networked media, as well as affording the possibility of an intensification of the critique from psychological and psychoanalytic perspectives on contradictions and tensions present in such contexts.